North Atlantic Regional Water Resources Study. Appendix C. Climate, Meteorology and Hydrology. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
The Purpose of this Appendix is to describe the Region from a Climatic, meteorologic and hydrologic viewpoint, and to provide hydrologic data, analyses and techniques necessary for the consideration of surface water problems and an evaluation of alternative solutions proposed for these and related problems. The analyses contained herein are consistent with the broad-scaled objectives of a framework water resources planning study. Appendix C includes descriptions of the North Atlantic Region's climatic and hydrologic environments and summaries of selected available data. Information is presented on existing surface water quantity and suitability, and on floods, droughts and existing regulation. Related aspects such as ground water and estuaries and coastal areas are also considered. Appendix C to report dated Jun 72, AD-A036 616. See also Appendix D, AD-A036 622.